Efficacy and safety of lenvatinib plus durvalumab combined with hepatic arterial infusion chemotherapy for unresectable intrahepatic cholangiocarcinoma - Zhao, Rongce; Zhou, Jing; Miao, Zhaoxia; Xiong, Xinhao; Wei, Wei; Li, Shaohua; Guo, Rongping (Frontiers in Immunology, 2024)
Background The prognosis for unresectable intrahepatic cholangiocarcinoma (ICC) is poor and the efficacy of traditional chemotherapy remains unsatisfactory. Hepatic arterial infusion chemotherapy (HAIC) with oxaliplatin, leucovorin, and 5-fluorouracil (FOLFOX) is effective in patients with unresectable ICC. In this study, we determined the preliminary clinical efficacy and safety of lenvatinib plus durvalumab combined with FOLFOX-HAIC in patients with untreated, unresectable ICC. Materials and methods Between July 2021 and July 2023, patients with unresectable ICC who initially received lenvatinib plus durvalumab combined with FOLFOX-HAIC at the Sun Yat-Sen University Cancer Center (SYSUCC) were reviewed for eligibility. Efficacy was evaluated by tumor response rate and survival, and safety was assessed by the frequency of key adverse events (AEs). Results A total of 28 eligible patients were enrolled. The objective response rates (ORRs) based on mRECIST and RECIST 1.1 criteria were 65.2% and 39.1%, respectively. The median OS was 17.9 months (95% CI, 5.7–30.1) and the median PFS was 11.9 months (95% CI, 6.7–17.1). Most patients (92.9%) experienced adverse events (AEs), whereas 46.5% (13/28) experienced grade 3 or 4 AEs. Conclusion Lenvatinib plus durvalumab combined with FOLFOX-HAIC showed promising antitumor activity and manageable AEs in patients with treatment-naive unresectable ICC. This regimen may be suitable as a novel first-line treatment option for this patient population.